Allogeneic hematopoietic stem cell transplantation versus hypomethylating agents in patients with myelodysplastic syndrome: A retrospective case–control study. Issue 3 (24th January 2013) - Jabbour, Elias; Mathisen, Michael S.; Garcia‐Manero, Guillermo; Champlin, Richard; Popat, Uday; Khouri, Issa; Giralt, Sergio; Kadia, Tapan; Chen, Julianne; Pierce, Sherry; Koca, Ebru; Daver, Naval; et al.
<x xml:space="preserve">Abstract</x> Allogeneic stem cell transplantation (allo‐SCT) is the only potentially curative treatment for myelodysplastic syndrome (MDS). Recently, hypomethylating agents (HMAs) have been shown to improve survival in patients with high‐risk MDS. We conducted a retrospective case–control study to compare survival with these treatment modalities in patients with untreated MDS. Controls were identified using a departmental database and transplant patients were matched in at least three of the following five criteria: year of diagnosis, age, blast percentage, International Prognostic Scoring System cytogenetic risk, and time from diagnosis to treatment. Median overall survival (OS) was 26 and 25 months for, respectively, allo‐SCT [(n = 53); range, 2–210 months] and HMA [(n = 40); range, 2–98 months] (P = 0.89). Four‐year survival rates were 24 and 23% for allo‐SCT patients and the nontransplant cohort, respectively. Patients undergoing allo‐SCT after 2000 had longer median OS compared with those transplanted before 2000 (41 versus 7 months, P=0.001). These results would suggest that prospective studies are needed to delineate the timing and efficacy of allo‐SCT in the HMA era. Am. J. Hematol. 88:198–200, 2013. © 2012 Wiley Periodicals, Inc.